Sphincter-preserving surgery for low rectal cancer: do we overshoot the mark? - Klose, Johannes; Tarantino, Ignazio; Kulu, Yakup; Bruckner, Thomas; Schmidt, Thomas; Schneider, Martin; Hackert, Thilo; Büchler, Markus W.; Ulrich, Alexis (Journal of gastrointestinal surgery, 2017)
PurposeIntersphincteric resection (ISR) is an alternative to abdominoperineal resection (APR) for a selected subset of patients with low rectal cancer, combining equivalent oncological outcome and sphincter preservation. However, functional results are heterogeneous and often imperfect. The aim of the present investigation was to determine the long-term functional results and quality of life after ISR.MethodsOne hundred forty-three consecutive patients who underwent surgery for low rectal cancer were analysed. Sixty patients received ISR and 83 patients APR, respectively. Kaplan-Meier estimate was used to analyse patients’ survival. The EORTC QLQ-C30, -C29 and the Wexner score were used to determine functional outcome and quality of life.ResultsISR and APR were both associated with comparable morbidity and no mortality. Patients’ disease- and recurrence-free survival after ISR and APR were similar (p = 0.2872 and p = 0.4635). Closure of ileostomy was performed in 73% of all patients after ISR. Long-term outcome showed a rate of incontinence (Wexner score ≥10) in 66% of the patients. Despite this, patients’ quality of life was significantly better after ISR compared to APR in terms of abdominal complaints and psycho-emotional functioning.ConclusionsISR is technically feasible with acceptable postoperative morbidity rates. Functional results following ISR are compromised by incontinence as the most important complication. However, long-term quality of life is superior to APR, which should be considered when selecting patients for ISR.
Gesehen am 14.09.2018